Two distinct neural pathways for mechanical versus digital technology - Giovanni Federico; Mathieu Lesourd; Arnaud Fournel; Alexandre Bluet; Chloé Bryche; Maximilien Metaireau; Dario Baldi; Maria Antonella Brandimonte; Andrea Soricelli; Yves Rossetti; François Osiurak (NeuroImage)
Technology pervades every aspect of our lives, making it crucial to investigate how the human mind deals with it. Here we examine the cognitive and neural foundations of technological cognition. In the first fMRI experiment, participants viewed videos depicting the use of mechanical tools (e.g., a screwdriver) and digital tools (e.g., a smartphone) compared to simple object movements. Results revealed a key dissociation: mechanical tools extensively activated the dorsal and ventro-dorsal visual streams, which are motor- and action-oriented brain systems. Conversely, digital tools largely engaged the ventral visual stream, associated with conceptual and social cognition. A second behavioral experiment showed a pronounced tendency to anthropomorphize digital tools. A third experiment involving a priming task confirmed that digital tools activate the social brain. The discovery of two different neurocognitive systems for mechanical versus digital technology offers new insights into human-technology interaction and its implications for the evolution of the human mind.